PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Manufaktur Sub Sektor Semen yang terdaftar Pada Bursa Efek Indonesia Periode 2015-2017) - Siti Harsiatun; Wahyu Hidayat (Universitas Diponegoro, 2019)
This study aims to determine the effect of capital structure and profitability on the firm's value of study in the cement sub-sector manufacturing companies listed on the IDX for the period 2015-2017. This study uses quantitative research methods. Data from this study uses secondary data in the form of company financial statements that are officially published by the Indonesia Stock Exchange (IDX) and the determination of samples using saturated sampling techniques. The capital structure indicators in this study are Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER). The profitability indicators in this study are Return on Assets (ROA) and Return on Equity (ROE). The indicator of company value in this study is Tobin’s Q Ratio. The population of this study is a cement sub-sector manufacturing company listed on the Indonesia Stock Exchange for the period 2015-2017. Analysis of the data used in this study is the Classical Assumption Test and Multiple Linear Regression Test. The results of this study explain that the independent variables DAR, DER, ROA and ROE partially have no significant effect on the dependent variable of firm value. Independent variables DAR, DER, ROA, and ROE simultaneously did not significantly influence the dependent variable of firm value.